Perancangan Robot Penyiraman pada Tanaman Tomat Beef (Lycopersicum esculentum Mill) menggunakan Metode Forward Chaining - Baginda siregar; Daren Sulistio (Jurnal Software Engineering and Computational Intelligence, 2026)
Plants, especially tomatoes, have high economic value and require regular maintenance, especially watering, to maintain optimal growth. This study developed an automatic tomato plant watering robot named "Farmbot" based on the forward chaining method, which allows for intelligent monitoring and regulation of water needs. The application of forward chaining as a rule-based expert system simplifies decision-making in watering, and this tool has the potential to be applied to other plants by reconfiguring environmental parameters. This study was conducted to prove the reliability of the forward chaining method in the process of designing a plant watering robot. The main microcontroller used in this study is the NodeMCU ESP32, then for the input device uses a soil moisture sensor to generate humidity data and a DS18B20 temperature sensor to generate temperature data on the soil. Various facts and rules are used to control the movement and watering process on the Farmbot robot. The results of this study show that the accuracy of the forward chaining method is 75.472% which is a good result and is not far from the fuzzy logic method which produces an MAE value of 4.5535 and has an accuracy value in the range of 92.149%. From these results, it can be concluded that the forward chaining method can be relied upon as a method for designing watering robots.